E-LEARNING USER INTERFACE ACCEPTANCE BASED ON ANALYSIS OF USER'S STYLE, USABILITY AND USER BENEFITS - Ramadiani .; Rodziah binti Atan; Mohd. Hasan Selamat; Noraini Che Pa; Rusli Abdullah (Jurnal Sistem Informasi, 2013)
E-learning does not function properly if the system is not in accordance with user needs. This study aims to establish an evaluation model for e-learning user interface according to user acceptance. The model is designed based on three categories: user learning style, usability and user benefits. Results of measurements of the three categories will determine the level of user acceptance of the e-learning interface. The data were taken using a questionnaire which was distributed to 125 ELS students from various countries. Then processed using SEM and Lisrel v8.80. This paper presents experimental set up for the general research and some results for technology acceptance theories.